Case Report: Exceptional Response to Second Line Temozolomide Therapy in a Patient With Metastatic Adrenocortical Carcinoma - Cosentini, Deborah; Turla, Antonella; Carminati, Ornella; Grisanti, Salvatore; Ferrari, Vittorio Domenico; Laganà, Marta; Rosti, Giovanni; Sigala, Sandra; Berruti, Alfredo (Frontiers in Endocrinology, 2021)
Background In a recently published retrospective case series, Temozolomide was found active as second line approach in advanced ACC patients. The disease control rate obtained, however, was short-lived. We report here an ACC patient with extensive metastatic disease who obtained a remarkable long lasting response with this alkylating agent. Case Presentation a 22-year-old female patient with ACC presented at our Medical Oncology Department in poor general condition due the presence of extensive metastatic pulmonary involvement. The disease had progressed to etoposide, doxorubicin and cisplatin plus mitotane therapy. Second line temozolomide therapy was prescribed leading to a progressive improvement of patient general conditions. The disease restaging after 12 cycles revealed a complete response of lung lesions and the patient was free from progression for 14+ months. Conclusion Temozolomide therapy could be exceptionally efficacious in the management of ACC patients. The molecular mechanisms of sensitivity and resistance to this drug should be carefully studied, in order to select the patients destined to obtain a significant clinical benefit to the drug.